2015
DOI: 10.1063/1.4926862
|View full text |Cite
|
Sign up to set email alerts
|

In-plane angular dependence of the spin-wave nonreciprocity of an ultrathin film with Dzyaloshinskii-Moriya interaction

Abstract: The nonreciprocal propagation of spin waves in an ultrathinPt/Co/Ni film has been measured by Brillouin light scattering. The frequency nonreciprocity, due to the interfacial Dzyaloshinskii-Moriya interaction (DMI), has a sinusoidal dependence on the in-plane angle between the magnon wavevector and the applied magnetic field. The results, which are in good agreement with analytical predictions reported earlier, yield a value of the DMI constant which is the same as that obtained previously from a study of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 26 publications
7
30
0
Order By: Relevance
“…It was also found that the frequency asymmetry exhibits a linear dependence as a function of k, and it becomes more pronounced when increasing the thickness of the heavy metal. The in-plane angular dependence of the frequency shift was also measured with BLS [73,75,86,87], which evidences a clear sinusoidal dependence with φ k , in agreement with Eq. 5.25, as predicted theoretically [96].…”
Section: Spin Waves In Thin Films With Interfacial Dmisupporting
confidence: 85%
See 2 more Smart Citations
“…It was also found that the frequency asymmetry exhibits a linear dependence as a function of k, and it becomes more pronounced when increasing the thickness of the heavy metal. The in-plane angular dependence of the frequency shift was also measured with BLS [73,75,86,87], which evidences a clear sinusoidal dependence with φ k , in agreement with Eq. 5.25, as predicted theoretically [96].…”
Section: Spin Waves In Thin Films With Interfacial Dmisupporting
confidence: 85%
“…The first observation of nonreciprocal spin waves [16,68,69] caused by interfacial DMI was achieved by Zakeri et al [70,71] using the spin-polarized electron energy loss (SPEEL) experimental technique. A few years later, nonreciprocal spin waves were observed by means of BLS spectroscopy in several ferromagnet/heavy metal interfaces [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. In agreement with the results of Zakeri et al [70,71], these numerous experiments have shown that interfacial DMI creates a noticeable frequency asymmetry in the spin-wave dispersion of counterpropagating Damon-Eshbach (DE) spin waves.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…We note that the value here is modest compared with that in the Pt/FM systems 19,20,22,23,31 . Nevertheless, the DMI on the annealed Ta/CoFeB structures is still of great interest for the study of skyrmions.…”
Section: /mentioning
confidence: 72%
“…According to Equation 1, a linear correlation exists between and , where the slope is determined by 23,31 . To further avoid possible instrument frequency offsets in the frequency difference between Stokes and anti-Stokes peaks, we subtract the values obtained by reversing the applied field as described by the following equation.…”
Section: Resultsmentioning
confidence: 99%